Bridging the gap between research and decision making: A European survey to enhance cooperation in wastewater-based epidemiology (WBE) for illicit drugs - Baz-Lomba, Jose Antonio; van Nuijs, AlexanderL N; Lenart-Boroń, Anna; Péterfi, Anna; de l'Eprevier, Anne; Löve, Arndís Sue Ching; Kasprzyk-Hordern, Barbara; Ort, Christoph; Simeoni, Elisabetta; Heath, Ester; Pridotkiene, Evelina; Lai, Foon Yin; et al. (Public health, 2025)
OBJECTIVES: Illicit drug use presents a significant challenge to global health and public safety, requiring innovative and effective monitoring strategies. This study aimed to evaluate the current landscape of wastewater-based epidemiology (WBE) for monitoring illicit drugs in Europe, focusing on collaboration, current practices, and barriers, while identifying opportunities for improvement. STUDY DESIGN: Cross-sectional survey-based study. METHODS: Coordinated by the Sewage Analysis CORe Group Europe (SCORE) and the European Union Drugs Agency (EUDA), two surveys were conducted in 2023 targeting researchers and stakeholders using WBE for illicit drugs. Data were analysed to identify trends, gaps, and opportunities for improving WBE implementation. RESULTS: The findings indicate a robust research infrastructure and diverse analytical methods among European institutions. Two-thirds of the participating countries reported using WBE data to inform policy. However, challenges persist, particularly in securing funding and coordination, as well as generating national estimates from multiple locations and addressing specific local policy needs. CONCLUSIONS: WBE has proven to be a valuable tool for monitoring illicit drug trends and informing drug policies. To unlock its full potential, sustained funding, methodological standardization, and enhanced cooperation are essential. This study provides critical insights into the European WBE landscape, offering a roadmap for strengthening the integration of actionable WBE data into public health and policy frameworks.
Keywords: poruchy spojené s užíváním psychoaktivních látek; zakázané drogy; Surveys and Questionnaires; Substance-Related Disorders; Humans; Illicit drugs; Decision Making; rozhodování; Wastewater-based Epidemiology; epidemiologie odpadních vod; lidé; Europe; Policy; Wastewater; průzkumy a dotazníky; Cooperation; Public health; Cross-Sectional Studies; New psychoactive substances; odpadní voda; Wastewater-Based Epidemiological Monitoring; Illicit Drugs; průřezové studie; Evropa